Groundwater hydrogeochemistry in permafrost regions. (25th April 2019) - Cochand, Marion; Molson, John; Lemieux, Jean‐Michel
Abstract: This review paper provides a summary of the current state of knowledge regarding groundwater hydrogeochemistry in permafrost regions and presents expected impacts of permafrost degradation on groundwater quality. Using published case studies, the most practical monitoring approaches are reviewed, possible monitoring issues are highlighted, and links between groundwater chemistry signatures and associated flow systems in northern climates are identified. Hydrogeochemical characteristics of groundwater in permafrost regions depend on the same reactions as in nonpermafrost regions, but in acting as a confining layer, permafrost can affect groundwater chemistry by restricting recharge and limiting exchange of energy and mass between the ground surface, surface water and groundwater. Rock (mineral)–water interactions can also increase due to longer residence times. The impacts of climate change on groundwater quality in permafrost regions are thought to be linked to the loss of this confining layer. Various studies have reported significant modifications in shallow and deep groundwater contributions to surface water, marked by a decrease in dissolved organic carbon and an increase in total dissolved solids in stream water linked to declining permafrost coverage. Future studies related to hydrogeology in permafrost areas should include better in situ hydrogeochemical characterization of groundwater to assess its potential for future use as the climate warms.